2015
DOI: 10.1523/jneurosci.5054-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced GABAA-Mediated Tonic Inhibition in Auditory Thalamus of Rats with Behavioral Evidence of Tinnitus

Abstract: in vitro, using the following three groups of adult rats: unexposed control (Ctrl); sound exposed with behavioral evidence of tinnitus (Tin); and sound exposed with no behavioral evidence of tinnitus (Non-T). Tonic GABA A R currents were evoked using the selective agonist gaboxadol. Months after a tinnitus-inducing sound exposure, gaboxadol-evoked tonic GABA A R currents showed significant tinnitus-related increases contralateral to the sound exposure. In situ hybridization studies found increased mRNA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 83 publications
2
46
0
Order By: Relevance
“…Decreased inhibition combined with increased excitation could result in hyperactivity of CN neurons that could be transmitted through the IC, or bypass the IC [60, 78], to the MGB. At the level of the MGB, however, there is little evidence of tinnitus-related decreases in GABAergic neurotransmission [79]. Rather, at this level, tinnitus measured with GPIAS was associated with increases in tonic extra synaptic GABAAR currents in action potentials/evoked bursts, and in GABAAR δ-subunit gene expression.…”
Section: Mechanisms Of Increased Sfr and Synchronymentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased inhibition combined with increased excitation could result in hyperactivity of CN neurons that could be transmitted through the IC, or bypass the IC [60, 78], to the MGB. At the level of the MGB, however, there is little evidence of tinnitus-related decreases in GABAergic neurotransmission [79]. Rather, at this level, tinnitus measured with GPIAS was associated with increases in tonic extra synaptic GABAAR currents in action potentials/evoked bursts, and in GABAAR δ-subunit gene expression.…”
Section: Mechanisms Of Increased Sfr and Synchronymentioning
confidence: 99%
“…Other studies using TTS models have correlated the GPIAS tinnitus index with other physiological or molecular changes and have shown that the greater the tinnitus index, the greater the likelihood of observing increased SFR or bursting in the CN and MGB [62] [86]. In addition, MGB neurons from animals with tinnitus fired more spikes per burst relative to non-tinnitus MGB neurons, suggesting a tinnitus-related increase in intrinsic membrane excitability [79]. …”
Section: Mechanisms Of Increased Sfr and Synchronymentioning
confidence: 99%
“…This finding, combined with evidence for structural and functional abnormalities in the prefrontal cortex of tinnitus patients (Leaver et al, 2011; Mirz et al, 2000; Schlee et al, 2009), led some authors to speculate that weakened projections from the prefrontal cortex to the auditory thalamic reticular nucleus, which sends GABAergic projections to the MGB, may limit the normal inhibitory control exerted over auditory thalamocortical signal transmission, thus increasing “auditory gain” (Lanting et al, 2014; Leaver et al, 2011; Rauschecker et al, 2010). This Gain Control Theory assumes that a decrease in GABAergic inhibition would be found in the thalamus of tinnitus sufferers, a supposition for which the data are mixed (Sametsky et al, 2015; Su et al, 2012, see below). Additional pathways from sites known to show tinnitus-related changes and that project to thalamus may also be involved.…”
Section: 0 Auditory Thalamus (Mgb)mentioning
confidence: 99%
“…The thalamocortical dysrhythmia model suggests that elevated inhibition acting at extrasynaptic GABA A Rs results in focal burst activity associated with abnormal low-frequency oscillations in thalamus. This ectopic disinhibition resulting in fast oscillatory activity in AI, can correlate with the percept of tinnitus (Llinas et al, 2006; Sametsky et al, 2015). GABAergic inhibition is thus critically involved in determining higher frequency thalamocortical oscillations as well as slow-wave sleep (Llinas et al, 2006).…”
Section: 0 Gabaa Receptorsmentioning
confidence: 99%
See 1 more Smart Citation